Impact of the Covid19 Outbreak on Macedonian Trade Flows - Iskra Stancheva Gigov (Institute of Economic Sciences, Belgrade, 2020)
Reduced demand and the disruptions in value chains, as a result of the COVID-19, are expected to have a significant impact on the external sector, especially in economies such as Macedonian, whose manufacturing sectors are more integrated into global supply chains. Hence, the main purpose of the paper is to see to what extent and in which segments the new conditions have reflected on exports and imports in the Macedonian economy, and to review the measures and activities taken in order to mitigate short-term challenges and facilitate cross-border trade. The paper analyzes the trend and the changes that occur both on the import and export side, in general, by selected products and by countries. The data generally refer to a last 5 years. For more particular and specific analyzes, they cover the period from January 2019 until June 2020, on a quarterly basis. The main used research methods are: analysis and synthesis, statistical, historical and inductive-deductive method. The results have shown that the decline in economic activity and demand globally, including in the European Union, and thus in the most important Macedonian export partners, directly affects export sector in the country. Economy also faces serious import problems, especially due to its heavy dependence on materials needed for industrial production processes that are usually imported from the hardest-hit markets in Europe. The trade measures are mainly designed to avoid unnecessary barriers to trade and disruption of global supply chains.
Keywords: export,import,COVID‐19outbreak,Macedonianeconomy